2022
DOI: 10.4218/etrij.2021-0084
|View full text |Cite
|
Sign up to set email alerts
|

An energy‐efficient technique for mobile‐wireless‐sensor‐network‐based IoT

Abstract: Wireless sensor networks (WSNs) are one of the basic building blocks of Internet of Things (IoT) systems. However, the wireless sensing nodes in WSNs suffer from energy constraint issues because the replacement/ recharging of the batteries of the nodes tends to be difficult. Furthermore, a number of realistic IoT scenarios, such as habitat and battlefield monitoring, contain mobile sensing elements, which makes the energy issues more critical. This research paper focuses on realistic WSN scenarios that involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…We utilized a T-test to determine the significance levels, considering a confidence interval of 95%. The results in tables [6][7][8] revealed that the performance improvements achieved by the NN_MH LEACH protocol were statistically significant, reinforcing the validity and reliability of the findings…”
Section: Limitations and Challengesmentioning
confidence: 60%
See 2 more Smart Citations
“…We utilized a T-test to determine the significance levels, considering a confidence interval of 95%. The results in tables [6][7][8] revealed that the performance improvements achieved by the NN_MH LEACH protocol were statistically significant, reinforcing the validity and reliability of the findings…”
Section: Limitations and Challengesmentioning
confidence: 60%
“…Figs. [6][7][8][9][10][11][12][13] Compare the performance of LEACH and NN_MH-LEACH mechanisms in terms of network lifetime, energy consumption, and packet delivery ratio. The results demonstrate the superiority of the proposed NN_MH LEACH protocol over the traditional LEACH protocol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, no random CH selection is done. Singla et al [51] proposed a CH selection algorithm for mobile sensor nodes with RF energy harvesting, using a K-means clustering algorithm. Dhanusha [52] proposed a Weighted Rendezvous Planning (WRP) algorithm to control the movement of mobile sink in WSN to reduce consumed energy.…”
Section: Energy Optimization-based Clustering Algorithmsmentioning
confidence: 99%